2020
DOI: 10.1029/2019gc008586
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the Deep Calabrian Subduction (Central Mediterranean Sea) From Wide‐Angle Seismic Data and 3‐D Gravity Modeling

Abstract: The Calabrian subduction zone is one of the narrowest arcs on Earth and a key area to understand the geodynamic evolution of the Mediterranean and other marginal seas. Here in the Ionian Sea, the African plate subducts beneath Eurasia. Imaging the boundary between the downgoing slab and the upper plate along the Calabrian subduction zone is important for assessing the potential of the subduction zone to generate megathrust earthquakes and was the main objective of this study. Here we present and analyze the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 107 publications
(208 reference statements)
2
20
1
Order By: Relevance
“…The AE T. Becker and an anonymous reviewer are thanked for the assistance and the useful suggestions, respectively. This paper is a Comment and bears mostly on the data available through Dellong et al, 2020.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The AE T. Becker and an anonymous reviewer are thanked for the assistance and the useful suggestions, respectively. This paper is a Comment and bears mostly on the data available through Dellong et al, 2020.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…As to differences in crustal thickness between the oceanic crust imaged along DY-P4 and DY-P3, the top of the oceanic crust along the DY-P3 velocity model was never shown in Dellong et al (2018) nor in Dellong et al (2020), as it was not directly observed in the DY-P3 OBS data. If the author of the comment is referring to the oceanic crust location presented in the gravity models, it is worth mentioning that this specific "best fit" model was built to fit the free-air gravity anomaly and consequently does not reflect our latest interpretation of the area.…”
Section: Oceanic Crustal Thickness Gravity Models and Figure 2 Of Tmentioning
confidence: 92%
“…We agree that the lower portion of the crustal block, initially interpreted as Calabrian continental crust along profile DY-P3, in fact represents oceanic crust of the downgoing Ionian Sea slab (Figure 1; Comment Key Point 2). We note in the text, "While along DY-P3 no slab was modeled, along the profile DY-P4, the slab is clearly imaged by the data from the land stations […] The Moho depth along model distance 80-120 km on profile DY-P3 (31 km) corresponds to the depth of the oceanic Moho along DY-P4; however, the backstop-slab interface was not detected along DY-P3 ( Figure 9 and Figure S6 in Dellong et al, 2020; electronic supplements)". This new interpretation is due to the better data quality of the well-coupled land stations than the sea bottom instruments.…”
Section: Alternate Interpretation Of the Calabrian Blockmentioning
confidence: 99%
See 2 more Smart Citations